Professores que ensinam matemática e a inclusão escolar: algumas apreensões - Rosa, Erica Aparecida Capasio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The intention of this research is to develop an understanding, through the narratives of teachers who teach mathematics, about school inclusion and the process of teaching and learning of mathematics students with disabilities, pervasive developmental disorders, high skills and giftedness. To produce the narratives we use the assumptions of Oral History routinely used by the group of História Oral e Educação Matemática (Ghoem). Interviews have been made and we used official data from Campinas, city where the research was made, in order to contextualize the location of this research. Our subject were nine teachers who teach mathematics wherein seven of them are graduated mathematics teachers and the other two are graduated in special education. In this sense we did an analysis of convergence/divergence were we highlight three themes that provide the tailpiece of our work. The first category was nominated At first look, we discussed the feeling of teachers entering the first time in your classroom and realize that there are student with disabilities in it; Here we also understand that we must consider the feelings of the teachers of special education when having to teach mathematic and others; Formation is the second topic addressed where we discussed the formation of mathematic teachers in relation to the special education, the formation of special education teacher in relation to the mathematics and also other reflections about the formation from the perspective of inclusive education. The last category was nominated What school is this? where we discussed what school is that we are seeking in the perspective of inclusive education. And from these analyzes, it was possible to understand that there is still resistance from teachers regarding the inclusion of students with disabilities, pervasive developmental disorders, high skills and giftedness but the majority was in favor of this new paradigm and this will only....

Esta pesquisa teve como objetivo elaborar uma compreensão, por meio das narrativas de professores que ensinam matemática, sobre a inclusão escolar e o processo de ensino e aprendizagem de matemática de alunos com deficiência, transtorno global do desenvolvimento, altas habilidades e superdotação. Para produzir as narrativas utilizamos os pressupostos da História Oral corriqueiramente usado pelo Grupo de História Oral em Educação Matemática (Ghoem), além das entrevistas usamos dados oficiais do município de Campinas, cidade lócus da pesquisa em questão, afim de contextualizar o local que foi realizada. Os nossos sujeitos foram nove professores que ensinam matemática sendo que sete deles são professores formados em licenciatura plena em Matemática e duas professoras de Educação Especial. Nesse sentido fizemos uma análise de convergência/divergência onde destacamos três categorias, ou seja, três temas que proporcionam o arremate de nosso trabalho. As categorias são: À primeira vista, discutimos sobre as sensações dos professores ao entrar pela primeira vez na sua sala de aula e perceber que nela existem alunos com deficiência; aqui também entendemos que cabem as sensações das professoras de educação especial ao ter que ensinar matemática, entre outras; Formação é o segundo tema abordado, em que discutimos a formação dos professores em relação à educação especial e também à formação em matemática das professoras de educação especial, além de outras reflexões sobre a formação sob a perspectiva da educação inclusiva; E o terceiro e último tema abordado nessa dissertação está relacionado à escola Que escola é essa?, em que discutimos que escola é essa que estamos buscando na perspectiva da educação inclusiva. E, a partir dessas análises, foi possível compreender que ainda existe resistência por parte dos professores em relação à inclusão de alunos com deficiência...
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Professores de matematica; Educação inclusiva; Inclusão em educação; Narrativas pessoais; Crianças deficientes - Educação; Historia oral; Campinas (SP)